Fabrication of fine particle powder from Teak (Tectona Grandis) leaves as a textile dyeing with environmentally friendly technology - Budianto, Arif; Dewi, Diah L.; Rahayu, Susi; Kurniawidi, Dian W.; Akhyar, Halil; Alaydrus, Alfina T. (Universitas Muhammadiyah Mataram, 2024)
Green technology for eco-friendly dyes in textile industries has been required in recent decades. An innovation was established by producing textile dyes from natural sources. This research aims to identify fine particle powder's characteristics and analyze the color changes applied to the textile. The mechanical thermal was utilized to produce natural dyes. Three main stages were conducted to obtain dye powder: mordant, coloring, and fixation. The dye powder was examined for water content, phytochemical tests, FTIR, SEM-EDX, and color using the Android-based Color Analyzer and Color Grab applications. The results show that the water content of 7.21% meets the SNI 01-3709-1995 standard. So, the powder can be stored for a long time because it does not quickly spoil. In addition, the phytochemical test resulted in alkaloids, flavonoids, and tannins. This revealed that teak leaf powder can be a suitable textile dye. After that, SEM-EDX examination illustrated that the powder had a round, flat, elongated morphology, a sharp edge texture, and an irregular position. Meanwhile, the EDX signified that the recognized chemical elements did not damage the environment, and the powder diameter ranges from 0.5-8.5 μm. The powder size complied with the fine particle powder category. To analyze the color from the dye powder application, there were color changes during each dyeing process. During all stages, from making the powder to applying the powder to the fabric, environmentally friendly technology was utilized. Therefore, this research can promote new opportunities for innovation and development of highly competitive products towards a more environmentally friendly and sustainable textile industry.